Workshop on Disability in America, a New Look : summary and background papers : based on a workshop of the Committee on Disability in America: a New Look, Board on Health Sciences Policy - Field, Marilyn J. (Marilyn Jane); Jette, Alan M.; Martin, Linda G., 1947- (National Academies Press, 2006)
Of workshop presentations and discussions -- Models and concepts of disability -- Trends in disability -- Disability across the age spectrum -- Secondary health conditions: Part I -- Secondary health conditions: Part II.